2012
DOI: 10.1108/00483481211263773
|View full text |Cite
|
Sign up to set email alerts
|

HR attributions and the dual commitment of outsourced IT workers

Abstract: PurposeOutsourced information technology (IT) workers establish two different employment relationships: one with the outsourcing company that hires them and another with the client organization where they work daily. The attitudes that an employee has towards both organisations may be influenced by the interpretations or attributions that employees make about the reasons behind the human resource (HR) management practices implemented by the outsourcing company. This paper aims to propose that commitment‐focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 55 publications
7
64
0
Order By: Relevance
“…Their study showed that the employees' perception towards the purpose of certain HR practices would influence their attitudes. Similar results were also seen in Fontinha et al (2012), with data derived from 158 outsourced IT workers in Portugal; and Sanders and Yang (2015) who did an experimental study with 354 employees from Dutch health care organizations.…”
Section: Literature Review Hr Attributions and Job Satisfactionsupporting
confidence: 67%
See 1 more Smart Citation
“…Their study showed that the employees' perception towards the purpose of certain HR practices would influence their attitudes. Similar results were also seen in Fontinha et al (2012), with data derived from 158 outsourced IT workers in Portugal; and Sanders and Yang (2015) who did an experimental study with 354 employees from Dutch health care organizations.…”
Section: Literature Review Hr Attributions and Job Satisfactionsupporting
confidence: 67%
“…The concept of HR attributions was first introduced by Nishii et al in 2008 and have been studied by only a few researchers so far (e.g. Fontinha et al 2012;Chen and Wang 2014;Sanders and Yang 2015). HR attributions refer to the employees' causal explanation or perception of why certain HR practices are adopted by the management within their organization.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research demonstrates that when employees attribute the implementation of HR practice to external factors, there is little or no effect on employee attitudes and behaviours (Koys, 1988;Nishii et al, 2008). However, when employees attribute the implementation of such practices to internal factors, it is more likely to affect their attitudes and behaviours (Fontinha et al, 2012;Koys, 1988;Nishii et al, 2008). Internal attributions are also multidimensional.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, employees can attribute HR practices favourably or unfavourably depending on their perceptions as to why specific HR practices are used. Research suggests that employees make external and internal attributions about the implementation of HR practices (Fontinha, Chambel, & De Cuyper, 2012;Koys, 1988;Nishii et al, 2008;Shantz, Arevshatian, Alfes, & Bailey, 2016). External attributions are when employees attribute the implementation of HR practices as a pressure from outside beyond the control of management (such as a union).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies found that employees' HRM attributions are significantly related to motivational states such as affective commitment (English & Chalon, 2011;Fontinha, Chambel, & De Cuyper, 2012) and job satisfaction , it remains unclear whether employee attributions of HRM motivate employees to engage in HRM coproduction.…”
Section: Antecedents To Hrm Co-production: the Role Of Hrm Attributionsmentioning
confidence: 99%